(3LQjeI GdEOYGA HJRhjQ Tjc aj VhA bGfhf GdJLGQI GdLOjO (B:s (3OQGSI ebGQfI HGdabg GdESdGej (B/s - (3CHh GdhaG, CHh GdhaG eMeOs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2007)
(3CSGS JLQje GdEOYGA HJRhjQ Tjc(B- (3GdEOYGA jJRhjQ Tjc(B- (3ShA fjI eOYj GdJRhjO(B- (3UOhQ Mce fgGFj HUMI GdTjc(B- (3GdYbhHI(B.s
Keywords: (3GdJRhjQs; (3GdbGfhf GdJLGQjs; (3LQGFe GdGehGds